Altering Charges on Heterobimetallic Transition‐Metal Carbonyl Clusters. Issue 54 (11th September 2020) - Unkrig, Wiebke; Kloiber, Konstantin; Butschke, Burkhard; Kratzert, Daniel; Krossing, Ingo
Abstract: The homoleptic group 5 carbonylates [M(CO)6 ] − (M=Nb, Ta) serve as ligands in carbonyl‐terminated heterobimetallic Ag m M n clusters containing 3 to 11 metal atoms. Based on our serendipitous [Ag6 {Nb(CO)6 }4 ] 2+ (4 a 2+ ) precedent, we established access to such Ag m M n clusters of the composition [Ag m {M(CO)6 } n ] x (M=Nb, Ta; m =1, 2, 6; n =2, 3, 4, 5; x= 1−, 1+, 2+). Salts of those molecular cluster ions were synthesized by the reaction of [NEt4 ][M(CO)6 ] and Ag[Al(OR F )4 ] (R F =C(CF3 )3 ) in the correct stoichiometry in 1, 2, 3, 4‐tetrafluorobenzene at −35 °C. The solid‐state structures were determined by single‐crystal X‐ray diffraction methods and, owing to the thermal instability of the clusters, a limited scope of spectroscopic methods. In addition, DFT‐based AIM calculations were performed to provide an understanding of the bonding within these clusters. Apparently, the clusters 3 + ( m =6, n =5) and 4 2+ ( m =6, n =4) are superatom complexes with trigonal‐prismatic or octahedral Ag6 superatom cores. The [M(CO)6 ] − ions then bind through three CO units as tridentate chelate ligands to the superatom core, giving overall structures related to tetrahedral AX4 (4 2+ ) or trigonal bipyramidal AX5 molecules (3 + ). Abstract : Anything is possible ! [Ag m {M(CO)6 } n ] x clusters (M=Nb, Ta; m =1, 2, 6; n =2, 3, 4, 5; x =1−, 1+, 2+) were synthesized by the reaction of [NEt4 ][M(CO)6 ] and Ag[Al(OR F )4 ] (R F =C(CF3 )3 ) and the structure determined by single‐crystal X‐ray diffraction methods. The [M(CO)6 ] fragments serve as ligands in the obtained clusters. DFT‐based AIM calculations were performed to provide an understanding of the bonding situation and the cores of the cations were interpreted as superatoms.